PEMBERDAYAAN PETERNAK SAPI POTONG DI DESA TIMBUOLO TENGAH MELALUI PENANAMAN RUMPUT GAJAH (Pennisetum Purpureum) - Muhammad Sayuti M.; Tri Ananda Erwin Nugroho; Laode Sahara; Fahrul Ilham (Universitas Jenderal Soedirman, 2020)
Elephant grass (Pennisetum purpureum) is a high nutritious forage that is often used as beef cattle main feed. This forage is easily cultivated, produces a lot of biomass, and can be harvested several times a year. This community service activity aimed at empowering the residents of Timbuolo Tengah Village, Botupinge sub-district, Gorontalo province to be able to independently and properly cultivate the elephant grass on land that was not utilized. The empowerment method used was giving theories indoor and continued with the practice of planting it on a demonstration plot of land. Stages of implementation included preparation (identification of partner problems, socialization of activity programs), implementation (extension of the grass cultivation, determination of demonstration land plots, land clearing, fencing around the land, preparation of the cuttings, planting and maintenance), and evaluation (behavior of the partners and their production of the planted grass). The observations of the behavior of a number of Central Timbuolo villagers showed a good response during the preparation until planting the grass. Some residents had been able to independently cultivate it on private land showing an increase in villagers' knowledge and skills. The grass planted on several demonstration plots of land grew well and was quite fertile. The palatability of beef cattle to the grass originating from the crop looked higher than other forages, it consumed more and the performance was better than before.